Meningkatkan Loyalitas Pelanggan: Dampak Experiential Marketing terhadap Niat Penggunaan Ulang pada Layanan Transportasi Gojek - I Gusti Ayu Imbayani; I Made Surya Prayoga (JURNAL AKADEMISI VOKASI, 2024)
The purpose of this study was to determine the effect of experiential marketing on Repeat Use Intention mediated by Customer Satisfaction. The population in this study were Gojek application users in the Denpasar area with an unknown number. Sampling in this study was conducted using non probability sampling with purposive sampling technique, so that the sample of this study was 108 people as respondents in the Denpasar area. Data collection techniques using a questionnaire. The data analysis technique uses Partial Least Square (PLS) analysis with the help of SmartPls v.4 software. The results showed that Experiential marketing has a positive effect on Repeat Use Intention, Experiential marketing has a positive effect on Customer Satisfaction, Customer Satisfaction has a positive effect on Repeat Use Intention and Customer Satisfaction is able to mediate the effect of Experiential marketing on Repeat Use Intention.